Implementation of BS Program at GPGC Timergara, KP, Pakistan: Students and Faculty Perceptions - Zada, Noor; Zada, Pir (The Lighthouse Journal of Social Sciences, 2023)
This study describes the implementation of Bachelor of Studies (BS) program at Government Postgraduate College Timergara Lower Dir, Khyber Pakhtunkhwa. The problems faced by the teachers and students in the initial stages of the implementation of the BS program has been discussed. The sample consisted of teachers and students from various academic disciplines. These disciplines included basic sciences, life sciences, numerical sciences, and social sciences. Data was collected through interviews with these participants. The interviews explored the views of students and teachers on a variety of topics related to the BS program, including its implementation, its significance, and the challenges faced by both students and teachers. The study revealed that although at the beginning there were so many problems in the implementation of BS program at GPGC Timergara, but with the passage of time, the BS program was successfully adopted and implemented. The demanding workload of the BS program presents a double-edged sword for teacher development. While the program's diverse and varied curriculum fosters professional growth, the rapid pace of assessments and result preparation leaves little time for teachers to actively pursue their own qualifications.